Análise da taxa de sobrevivência de implantes dentários com diferentes tipos de conexões - Cerqueira Filho, José Ribamar de Almeida (2017)
There are important indicators that have been established for implant dentistry, such as the success rate and survival of implants. There is no consensus on which implant connection geometry is more favorable for the preservation of bone tissue; in addition, what type of connection would present a lower rate of complications of implant prostheses. Therefore, this project aimed to perform a systematic review with meta-analysis, in order to study the failure rates of implants and peri-implant bone loss in implants with different types of connections (Morse taper and external hexagon). The databases PubMed/Medline, Cochrane Collaboration and SciELO were analyzed in order to select the studies published in the area using the descriptors: “Dental Implants” and “External connection” and/or “Internal conical connection”; “Morse connection”. The data were organized and analyzed using the software Reviewer Manager 5.3, being considered a significant value of p <0.05. The software Reviewer Manager 5.3 performed the meta-analysis. The collected data indicated that there was no significant difference in the loss of dental implants to compare the number of implants installed with external hexagon and morse taper implants (p = 0.85). However, implants with an external hexagon connection showed a higher rate of peri-implant bone loss when compared to implants with a Morse-taper connection (p = 0.03), it was not possible to identify a significant difference in the complication rates between the tested connections (p = 0.41). Based on the results presented, it was possible to conclude that both connections are viable, but the internal conical connection of the Morse type presented less peri-implant bone loss. This research presented the objective of analyzing the distribution of tensions in three-dimensional models with different types of connections of dental implants. The models with external hexagon connection, internal hexagon and cone-morse were elaborated. The FEMAP software was used for preparation of meshes, conditions and restrictions axial and oblique load. A qualitative analysis of the results was carried out using FEMAP software. The main results were analyzed by means of von Mises stress maps (MPa) and interpreted in order to establish a protocol for indicating the best type of implant connection for low density bone tissue. The data allow us to conclude that the oblique loading generated a higher concentration of stresses. Thus, as internal connections have played a more significant role in the distribution of stress as compared to external connections